On Taxes and Inflation - Morag, Amotz (New York : Random House, 1965)
This study breaks new grounds by treating inflation as a form of taxation, and by considering the impact of price increases caused by tax measures on the welfare of the citizen.
Includes bibliographical references.
osc 13/06/17
Loans
Keywords: Taxation; Inflation (Finance)